The correlation between on-farm biosecurity and animal welfare indices in large-scale turkey production - László Kovács; Christopher René Klaucke; Máté Farkas; Mikolt Bakony; Viktor Jurkovich; László Könyves (Poultry Science)
This research aimed to determine the association between biosecurity and animal welfare measures in large-scale fattening turkey farms in Hungary. Large-scale farms raising male fattening turkeys across Hungary were contacted, with 24 agreeing to participate. The Biocheck.UGent questionnaire was used to evaluate biosecurity measures, and Animal Welfare Indicators (AWIN) protocol was used for welfare assessment. The association between biosecurity and welfare indicators was investigated by correlation testing and prediction accuracy using random forest classification. The areas of biosecurity that were shown to be closely linked to the welfare index were the organization of the farm (farm management, supply of materials), the control and hygienic measures implemented between farm structures, cleaning and disinfection measures on the farm, and control and hygienic measures implemented in the case of farm workers and visitors upon entrance and exit. The study highlighted the link between biosecurity and animal welfare in turkey production, concluding that enhanced biosecurity measures correlate with better welfare outcomes and emphasizing the need for comprehensive and well-implemented biosecurity protocols.